Estudo de pórticos preenchidos com alvenaria - Madia, Fernando César Alvarenga Rosa (Universidade Federal de São Carlos, 2012)
This work proposes to develop a study about frame structure behaviour filled with masonry panel, for the purposes of building bracing. It aims to consider the hardening of this filling masonry in the frame which deals with the horizontal loadings analysis such as wind strength. The work starts with the historical development, depicting the fact that who started this study. Then, variables which influence the frame rigidity are shown, like: wedging, the kind of link between panel- frame, panel openings, codes and design specification. These topics describe theoretical and experimental studies that have already been carried out about the theme and the main approaches considered by the researchers. For the purpose of checking the structure stiffening increase some case study were held. The first one comprehends a simple frame, theoretical, with data and results obtained from specialized literature. The second one compares a steal frame tested on a laboratory, with a computer program modeled frame, using the same features as the real stuff. Then, the portics were analysed with different filled floors. For doing so, different available calculation methods were applied, which employ equivalent diagonal concept to consider the masonry filling contribution as a structural constituent. Bearing in mind to verify the stiffening increase when the filling masonry are considered, a real building was modeled, in this particular case Helena Building, it has 22 floors, built in São Paulo using reinforced concrete, either considering or not the filling masonry. As the research bottom line, this text allows an updating about the possibility of including the filling masonry in building projects, an evaluation of the stiffening increase that the masonry might cause, an analysis to verify the compressed diagonal model and finally it shows design criteria.
Study Masonry Infilled Frame
Keywords: Alvenaria; Pórticos estruturais; Cálculo - método; Alvenaria de enchimento; Pórtico preenchido; Diagonais equivalentes; Masonry infill; Infilled frame; Equivalent diagonal; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL